2008
DOI: 10.1507/endocrj.k08e-077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alanine Aminotransferase, White Blood Cell Count, and Uric Acid in Their Association with Metabolic Syndrome: A Study of Korean Adults

Abstract: Abstract. The aim of this study is to investigate the respective associations of alanine aminotransferase (ALT), white blood cell (WBC) count, and uric acid with metabolic syndrome and compare the magnitude in their association with metabolic syndrome, using modified Adult Treatment Panel III (ATP III) and its components. We studies 5,020 Korean adults (20-70 years of age; 2,501 men and 2,519 women) who visited Center for Health Promotion in Pusan National University Hospital for routine health examinations. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
2
16
1
2
Order By: Relevance
“…In this study, TC and HDL eventually enter into the linear regression models, which is most likely result from that TC and HDL may be more relevant with stroke in Asian populations. UA was significantly and independently associated with neutrophil, WBC counts, and with HDL-C, which plays an important role in inflammation and atherosclerosis not only in general population [29,46,47] but also in subclinical thoracic atherosclerosis [4] and metabolic syndrome [5]. Consistent with previous studies, increased levels of UA showed higher concentrations of neutrophils and WBCs, except for those in the grade 1 group.…”
Section: Int J Neurosci Downloaded From Informahealthcarecom By Univsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, TC and HDL eventually enter into the linear regression models, which is most likely result from that TC and HDL may be more relevant with stroke in Asian populations. UA was significantly and independently associated with neutrophil, WBC counts, and with HDL-C, which plays an important role in inflammation and atherosclerosis not only in general population [29,46,47] but also in subclinical thoracic atherosclerosis [4] and metabolic syndrome [5]. Consistent with previous studies, increased levels of UA showed higher concentrations of neutrophils and WBCs, except for those in the grade 1 group.…”
Section: Int J Neurosci Downloaded From Informahealthcarecom By Univsupporting
confidence: 88%
“…Recent clinical and experimental studies of a large population-based sample have shown that UA is correlated positively and significantly with inflammatory markers such as neutrophils, C-reactive protein (CRP), and high-sensitivity CRP (hs-CRP) [2,3]. Some clinical studies demonstrated that UA with white blood cells (WBCs), hs-CRP, and some lipoprotein was indepen-dently and positively associated with subclinical thoracic atherosclerosis [4] and metabolic syndrome [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gkrania-Klotsas et al reported that the combined relative risk (comparing the top to bottom tertiles of the WBC counts) was 1.61 (95% CI: 1.45-1.79, p50.001) [9]. In addition, Kang et al [28] found that WBC count significantly correlated with HOMA-IR in Korean adult women. Possible mechanisms underlying this phenomena may include interruptions in insulin signaling in the liver by inflammatory molecules such as IL-6 [29] or a pro-inflammatory effect on insulin [30], or insulin resistance [31,32].…”
Section: Discussionmentioning
confidence: 97%
“…El impacto del sedentarismo en la población no deja de ser importante, considerando que es una de las condicionantes que contribuye a que por medio del bajo gasto energético de un individuo, en conjunto con ingestas alimentarias normales o elevadas, se provoque un desbalance energético que se puede traducir en alteraciones del estado de salud, como la malnutrición por exceso. Todo esto recrudece el impacto en la comunidad, originado de la pandemia en que se ha convertido la obesidad (Buhring et al, 2009), y el denominado síndrome metabólico , que comprende un conjunto de factores de riesgo tales como; Dislipidemias, tensión arterial elevada, resistencia a la insulina, obesidad abdominal que incrementan el riesgo de enfermedad cardiovascular (Kang et al, 2008), constituyendo un estado de alto riesgo de morbilidad y mortalidad por enfermedades del corazón y diabetes, y las personas sedentarias son particularmente susceptibles a padecerlo. Aunque a nivel nacional e internacional se han desarrollado diversas investigaciones respecto a la valoración antropométrica de distintas poblaciones y rangos etáreos, es importante continuar desarrollando estudios que permitan evidenciar lo que sucede con una población generalmente no considerada y que permita desarrollar conocimiento relevante para la toma de decisiones frente a las políticas de salud o educación referidas al sedentarismo, el sobrepeso y la obesidad de las personas con discapacidad.…”
Section: Introductionunclassified
“…El impacto del sedentarismo en la población no deja de ser importante, considerando que es una de las condicionantes que contribuye a que por medio del bajo gasto energético de un individuo, en conjunto con ingestas alimentarias normales o elevadas, se provoque un desbalance energético que se puede traducir en alteraciones del estado de salud, como la malnutrición por exceso. Todo esto recrudece el impacto en la comunidad, originado de la pandemia en que se ha convertido la obesidad (Buhring et al, 2009), y el denominado síndrome metabólico , que comprende un conjunto de factores de riesgo tales como; Dislipidemias, tensión arterial elevada, resistencia a la insulina, obesidad abdominal que incrementan el riesgo de enfermedad cardiovascular (Kang et al, 2008), constituyendo un estado de alto riesgo de morbilidad y mortalidad por enfermedades del corazón y diabetes, y las personas sedentarias son particularmente susceptibles a padecerlo. …”
unclassified